2022
DOI: 10.1101/2022.11.14.22282297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Genome Sequence Data to Predict SARS-CoV-2 Detection Cycle Threshold Values

Abstract: The continuing emergence of SARS-CoV-2 variants of concern (VOCs) presents a serious public health threat, exacerbating the effects of the COVID19 pandemic. Although millions of genomes have been deposited in public archives since the start of the pandemic, predicting SARS-CoV-2 clinical characteristics from the genome sequence remains challenging. In this study, we used a collection of over 29,000 high quality SARS-CoV-2 genomes to build machine learning models for predicting clinical detection cycle threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Recently, Duesterwald et al [12] used genome sequence data and a machine-learning approach to predict cycle threshold (Ct) values of SARS-CoV-2 infections based on the k -mers. Similar to our findings, they suggested that S:L452 and P681 were hallmarks of VOCs, implying impacts on the observed Ct values in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Duesterwald et al [12] used genome sequence data and a machine-learning approach to predict cycle threshold (Ct) values of SARS-CoV-2 infections based on the k -mers. Similar to our findings, they suggested that S:L452 and P681 were hallmarks of VOCs, implying impacts on the observed Ct values in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies could inform predictive early warning public health systems regarding the emergence of potentially highly transmissible viral strains based on their constellation of mutations. Recently, Duesterwald et al [12] used genome sequence data and a machine-learning approach to predict cycle threshold (Ct) values of SARS-CoV-2 infections based on the k-mers. Similar to our findings, they suggested that S:L452 and P681 were hallmarks of VOCs, implying impacts on the observed Ct values in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations